Peran Perempuan dalam Iklan Televisi di Indonesia-Malaysia - Triwardhani, Ike Junita; Listiani, Endri; Putra, Raditya Pratama (Jurnal Common, 2021)
It is common to see advertisements that are almost the same between advertisements in Indonesia and those in Malaysia. Apart from the fact that we are allied, so many cultures and customs in Indonesia occur in Malaysia. This can be seen from the same advertisements using the concept of family, the role of women or housewives or using women as the main element to attract advertisements. Women who sit as a vehicle for promotion, because women are the target of the product or women who sit easily. Of the many advertisements that use women as advertising models, almost all of the female models used are women who are beautiful, have sexy bodies and are used beautifully. This then makes women even think that a beautiful symbol as depicted in an advertisement in a media, so that finally the body becomes the center of consciousness. It is not wrong, but how the meanings of the advertisement are seen and seen in particular seems to be an interesting study. The purpose of this study is to examine the roles of women depicted in television commercials (TVC) in Indonesia and Malaysia. This study uses a qualitative descriptive method, which describes how women are depicted in advertisements in Indonesia and in Malaysia. There will be several product advertisements that are selected. Then we will look at the role of women and what differences are used to describe women in the Indonesian version of product advertisements and the Malaysian version in television commercials.